Single camera 3D planar Doppler velocity measurements using imaging fibre bundles - Charrett, Thomas O. H.; Ford, Helen D.; Tatam, Ralph P. (IOP Publishing, 2006)
Two frequency planar Doppler Velocimetry (2ν-PDV) is a modification of the Planar Doppler Velocimetry (PDV) method that allows velocity measurements to be made, quickly and non intrusively, across a plane defined by a laser light sheet. In 2ν-PDV the flow is illuminated sequentially with two optical frequencies, separated by about 700MHz. A single CCD viewing through an iodine absorption cell is used to capture images under each illumination. The two images are used to find the normalised transmission through the cell, and the velocity information is encoded as a variation in the transmission Use of a single camera ensures registration of the reference and signal images and removes issues associated with the polarization sensitivity of the beam splitter, which are major problems in the conventional approach. A 2ν-PDV system has been constructed using a continuous-wave Argon ion laser combined with multiple imaging fibre bundles, to port multiple views of the measurement plane to a CCD camera, allowing the measurement of three velocity components.
2nd International Conference on Optical and Laser Diagnostics, 11-14 September 2005, City University, London, UK
Keywords: Planar Doppler velocity; PDV